Evaluation of rainwater harvesting system with shared built tank in housing development in tropical climate - Jahn Kassim, Puteri Shireen (2019)
The research aims to firstly, investigate the discrepancy between estimated performance and actual performance after occupancy; and secondly, to estimate the lifecycle saving of the rainwater harvesting system lifetime duration. The research focuses on Mesra Terrace Development in Kuala Lumpur as a case study. The study employed a quantitative method for the data collection. The empirical assessment of the after occupancy performance is based on the analysis of water consumptions and savings in both designed and operational phases. The findings indicate that the Rainwater harvesting system has met water efficiency target but did not meet the life-cycle savings target.